(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
Intuitionistic fuzzy T1 spaces are defined and studied in this paper. Eight new notions of intuitionistic fuzzy T1 spaces are defined and some relationship among them has been investigated. Some relations between the defined notions and other given notions of intuitionistic fuzzy T1 spaces has also been investigated. Under some conditions it is observed that image and preimage preserve intuitionistic fuzzy T1 spaces. Hereditary and productive property of such spaces has been also investigated. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 73-85, 2018